2021
DOI: 10.1039/d1cc01851e
|View full text |Cite
|
Sign up to set email alerts
|

Short-wavelength ultraviolet dosimeters based on DNA nanostructure-modified graphene field-effect transistors

Abstract: Direct and sensitive short-wavelength ultraviolet (UVC) dosimeters could enable safer disinfection environment against virus. We develop direct, quantitative, specific and highly sensitive UVC dosimeters based on DNA nanostructure-modified graphene field-effect...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, high temperatures are not suitable for the attachment of aptamers due to degradation of biomolecules. On the other hand, the UV degradation rate of DNA is a function of irradiation wavelength, with the observed degradation even at a dose of 0.1 kJ/m 2 at 254 nm irradiation, while staying stable at a dose of 120 kJ/m 2 in the case of irradiation at 365 nm UV [ 23 ]. Recent results showed that the irradiation of aptamers with 266 nm UV causes lesions with a relatively low damage rate, with a decay constant of about 0.4–0.8 h −1 , for an exposure rate at 2 mJ cm −2 s −1 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, high temperatures are not suitable for the attachment of aptamers due to degradation of biomolecules. On the other hand, the UV degradation rate of DNA is a function of irradiation wavelength, with the observed degradation even at a dose of 0.1 kJ/m 2 at 254 nm irradiation, while staying stable at a dose of 120 kJ/m 2 in the case of irradiation at 365 nm UV [ 23 ]. Recent results showed that the irradiation of aptamers with 266 nm UV causes lesions with a relatively low damage rate, with a decay constant of about 0.4–0.8 h −1 , for an exposure rate at 2 mJ cm −2 s −1 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sensing events and signal conversion normally occur at heterogeneous interfaces. ,, In the field of FETs, 2D materials restrain charge flow solely on the surface, which directly exposes it to the environment and is entirely located at the interfaces of signal acquisition and conversion, leading to rapid and sensitive response upon exposure to the outer stimuli. ,, In detail, the advantages of 2D FET sensors are attributed to at least three aspects: (i) The free dangling bonds enable 2D materials to construct functional heterostructures with ideal vdW interfaces readily. It reduces the scattering center, which is key to maintain their attractive electronic properties (e.g., high carrier mobility) even after different device fabrication and modification processes . (ii) The atomic thickness ensures direct exposure of the channel to functional interfaces and/or external environments, leading to a rapid response to foreign stimuli with ultrahigh sensitivity. (iii) The large surface-to-volume ratio provides abundant modification sites for anchoring specific receptors, which ensures the sensitivity and specificity upon specific perturbations. This section clarifies the motivation of using 2D materials, the concepts, and the fundamentals of the 2D FET sensors.…”
Section: Fundamentals and Motivationmentioning
confidence: 99%
“…Copyright 2017, Nature Publishing Group. c Reproduced with permission [ 32 ]. Copyright 2021, Royal Society of Chemistry.…”
Section: Sensing Mechanisms In Detecting Biomoleculesmentioning
confidence: 99%